Increasing Students’ Ability in Speaking by Using Video Blogs Media at the Seventh Grade of SMP Swasta Bunga Mawar Gunungsitoli in 2023/2024 - Fau, Sri Wahyuni; Laoli, Adieli; Maru'ao, Nursayani; Daeli, Hidayati (ITScience (Information Technology and Science), 2024)
The ability to speak is an expression of expressing opinions, thoughts and feelings in communicating and expressing oneself through interactions between people. Speaking is the basis for students to be confident in developing their potential in learning, especially learning English. This researcher aims to improve students' speaking skills by using video blog media. The method used in this research is the classroom action research method. The instrument of this research is the use of media through video blogs. The classroom action research carried out consisted of two cycles. Each cycle consists of 4 stages, namely planning, action, observation and reflection. The research results showed that in cycle I there were 26 students who achieved a score of less than 70 as the limit for complete understanding, while 4 students scored more than 70. The average score for students' speaking ability through video blogs was 54.33%. Meanwhile, in cycle II, 2 students got a score of less than 70, while 28 students got a score of more than 70. The average score for students' speaking ability through video blogs was 80.28%. After conducting classroom action research at Bunga Mawar Gunungsitoli Private Middle School, this provides an illustration that learning using media through video blogs has improved students' speaking skills, especially in class VII at Bunga Mawar Gunungsitoli.